The gigantic comet bernardinelli-bernstein: a review - Salem, Mohamed Khalil; Said, Mohamed; Osman , Hesham; Khaled, Mohamed; Khaled, Nada; El-sedafy, Shahd; Ibrahim, Ahmed (International Journal of Advanced Astronomy, 2023)
Huge comets are considered as serious threat to Earth. Bernardinelli-Bernstein (BB) comet is one of such huge comets. Based on the gath-ered data using space telescopes, scientists and astronomers have confirmed the fact that, the BB comet (C/2014 UN271) is the biggest comet ever seen. In this paper, we give a short review about the BB comet and we are trying to answer the question, does the comet BB pose a real threat to Earth?